A Study on the Mixing Characteristics of Thin Liquid Film Flows over Horizontal Spinning Disk Surface. (2016) - Majnis, Mohd Fadhil; Azudin, Nurhazwani Yusoff; Shukor, Syamsul Rizal Abd; Ahmad, Abdul Latif
Abstract: A reactor based on spinning disk technology offered an intensified mass transfer and rapid mixing in the liquid film with short liquid residence time. This paper reports the outcome of the experimental study of mixing visualization by dye tracer that carried out in a spinning disk test rig to compare with computational fluid dynamics (CFD) simulation of mixing by particle injection. The qualitative comparison used to visualize the influence of disk rotational speed on the mixing characteristics showed the identical pattern of dye particle distribution over the spinning disk surface. Further, the mechanistic model of the mixing characteristics of thin liquid films based on convective-diffusion equation is compared with the mathematical model by Tsibranska et al. (2009). The comparison shows the identical trend of the increment of the average of mass transfer coefficient as the disk rotational speed increases.